2009
DOI: 10.1002/hep.23279
|View full text |Cite
|
Sign up to set email alerts
|

Increased caffeine consumption is associated with reduced hepatic fibrosis

Abstract: Although coffee consumption has been associated with reduced frequency of liver disease, it is unclear whether the effect is from coffee or caffeine and whether there is an effect on hepatic fibrosis specifically. This study was undertaken to use a food-frequency instrument for dietary caffeine consumption to evaluate the relationship between caffeine intake and liver fibrosis. Patients undergoing liver biopsy completed a detailed caffeine questionnaire on three occasions over a 6-month period. Caffeine intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
188
3
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(208 citation statements)
references
References 26 publications
9
188
3
5
Order By: Relevance
“…In various studies including a large prospective study, patients with HCV-related liver disease with a regular coffee consumption show a lower rate of disease progression such as hepatic fibrosis [131][132][133] and HCC [134][135][136][137][138] . Recently, it was also reported that more than 3 cups per day coffee drinkers are three times more likely to have a virological response to peginterferon plus ribavirin treatment than non-drinkers [139] .…”
Section: Coffee Consumptionmentioning
confidence: 99%
“…In various studies including a large prospective study, patients with HCV-related liver disease with a regular coffee consumption show a lower rate of disease progression such as hepatic fibrosis [131][132][133] and HCC [134][135][136][137][138] . Recently, it was also reported that more than 3 cups per day coffee drinkers are three times more likely to have a virological response to peginterferon plus ribavirin treatment than non-drinkers [139] .…”
Section: Coffee Consumptionmentioning
confidence: 99%
“…Work of Ruhl and Everhart [17] has reported that the relationship between caffeine intake and reduced serum ALT levels was of prime importance than that for coffee. Sharp and Benowitz [18] have suggested that caffeine administration and serum level of caffeine were related to decreased levels of GGT however, studies performed in animals have provided data that caffeine has been effective in inhibiting chemical induced carcinogenesis [19]. Liver enzymes level may be affected by coffee components.…”
Section: Role Of Caffeinementioning
confidence: 99%
“…Coffee consumption has also suggested to be related to lower severeness of liver problems and lower speed of liver disease progression [17,52,53]. Epidemiological data obtained from studies have strongly suggested that consumption of coffee is defensive against hepatocellular carcinoma (HCC) as well as chronic liver disease (CLD) [18,[54][55][56][57][58][59]. There are hundreds of compounds in coffee, namely caffeine, diterpenes, potassium, niacin,magnesium, antioxidants, chlorogenic acids and tocopherols [60].…”
Section: The Mechanism Of Coffee's Hepatoprotective Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…In the two last study conducted by The National Health and Nutrition Examination Survey (NHANES) I and III, its was reported that high coffee consumption (more than two cups per day) were strongly associated with lower risk in increase transaminase enzyme and chronic liver disease. 2 Chronic liver disease, such as cirrhosis and hepatocellular carcinoma, were a highly morbidity and mortality disease. Patient with those end stage liver disease have a higher risk of liver failure, even 80% among them could lead to hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%